Crizotinib for the treatment of non-small-cell lung cancer with ALK gene rearrangements. (September 2012) - Alamgeer, Muhammad; Rogers, Toni-Maree; Fox, Stephen B; Solomon, Benjamin
Approximately 2–5% of non-small-cell lung cancers (NSCLC) contain rearrangements in the ALK gene. These tumors most frequently occur in younger, never or light smokers with adenocarcinoma and are typically independent of EGFR or KRAS mutations. Crizotinib is a small molecule inhibitor of the ALK tyrosine kinase that has demonstrated clinical activity in advanced ALK rearranged NSCLC patients with a response rate of 51–61% in a Phase I and II study with an estimated median progression-free survival of approximately 10 months. On the basis of this data the US FDA approved crizotinib for the treatment of ALK rearranged NSCLC in August 2011. In this article we review the clinical and pathologic features associated with ALK gene rearrangements in NSCLC, diagnostic assays for ALK gene rearrangements, the safety and efficacy of crizotinib, and outline remaining challenges in this population including the problem of acquired resistance.